A method for producing L-glucan and L-glucanone from waste sponge-derived carbon-based solid acid-catalyzed pyrolysis of biomass.

By modifying the waste sponge into a carbon-based solid acid catalyst, catalyzing the pyrolysis of biomass, the problem of waste sponge treatment is solved, and efficient conversion to levoglucan and levoglucose ketone is achieved, which is environmentally friendly and economically feasible.

CN116274248BActive Publication Date: 2025-04-15GUANGZHOU INST OF ENERGY CONVERSION CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310154175.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-23
Publication Date
2025-04-15
Estimated Expiration
2043-02-23

AI Technical Summary

Technical Problem

Waste sponges are difficult to efficiently handle during recycling. Direct combustion will release toxic gases, pose a threat to the environment, and lack effective resource conversion channels.

Method used

By passing the waste sponge through high temperature carbonization and acid treatment, it is modified into a carbon-based solid acid catalyst, which is used to catalyze pyrolysis of biomass and convert it into levoglucan and levoglucoseketone.

Benefits of technology

The coordinated coupling transformation of waste sponge and biomass is realized, and high value-added LG/LGO chemicals are generated, which avoids the environmental pollution caused by direct combustion of waste sponge, and provides a comprehensive recycling and utilization of scrapped cars and agricultural and forestry waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004091702680000101
    Figure BDA0004091702680000101
Patent Text Reader

Abstract

The present invention discloses a method for converting waste sponge-derived carbon-based solid acid into levoglucosan and levoglucosone by catalytic pyrolysis of biomass. The method utilizes the rich nitrogen-containing functional groups and porous structure of waste sponge to obtain waste sponge-derived carbon-based solid acid as a catalyst for biomass pyrolysis through carbonization, acid treatment and other processes, and converts biomass into chemicals such as LG / LGO with high added value, providing a new idea for the comprehensive recycling of biomass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention relates to the technical field of waste treatment, and in particular to a method for converting waste sponge-derived carbon-based solid acid-catalyzed pyrolysis of biomass into levoglucosan and levoglucosone. Background technology:

[0002] The rapid rise of the new energy vehicle industry has directly led to an increase in the number of scrapped cars year by year. In the comprehensive recycling of scrapped cars, non-metallic components have always been a difficult point in recycling. Compared with other non-metallic structures, waste seats have the largest volume share, and the filler is waste sponge. Waste sponge is mainly composed of polyurethane and polystyrene. Direct combustion will release a large amount of styrene and toxic gases containing cyanide, accompanied by the emission of typical greenhouse gases such as CO2, which will pose a serious threat to the environment and ecology. Therefore, it is of great significance to recycle waste sponge in a clean and efficient manner.

[0003] Biomass is considered to be a renewable carbon source that is expected to replace petroleum. After catalytic pyrolysis, the long molecular chains of lignocellulosic biomass can be converted into various small molecule products through a series of processes such as depolymerization, deoxygenation, reduction, aromatization, and reforming. Among them, levoglucosan (LG) and levoglucosone (LGO) are the most representative monomer derivatives and have extremely high product added value. Summary of the invention:

[0004] The purpose of the present invention is to provide a method for converting waste sponge-derived carbon-based solid acid-catalyzed pyrolysis of biomass into levoglucosan and levoglucosone, wherein the nitrogen-containing waste sponge is modified by high-temperature carbonization and acid treatment to obtain a rich The carbon-based solid acid catalyst with acidic sites catalyzes the pyrolysis of lignocellulosic biomass raw materials, converting the biomass into high value-added levoglucosan (LG) and levoglucosone (LGO), realizing the synergistic coupling transformation of waste sponge and biomass, and providing a new harmless and resource-based transformation pathway for the comprehensive recycling of scrapped automobile organic residues and agricultural and forestry waste biomass.

[0005] The present invention is achieved through the following technical solutions:

[0006] A method for converting waste sponge-derived carbon-based solid acid-catalyzed pyrolysis of biomass into levoglucosan and levoglucosone, the method comprising the following steps:

[0007] (1) The waste sponge from scrapped car seats is washed, dried, and crushed, and then sent into a tube furnace. The temperature is raised to 450-850°C, preferably 550-650°C, at a heating rate of 10°C / min under an inert atmosphere, and kept warm for 1-6 hours to carbonize it. After the carbonization is completed, it is taken out and ground, and then excess deionized water is added to stir and filter. This step is repeated three times, and the filter cake is collected and vacuum dried at 80°C for 12 hours, then taken out and ground again to obtain a waste sponge-derived porous carbon material;

[0008] (2) using an ultrasonic impregnation method to load the porous carbon material prepared in step (1) with phosphate groups, the specific steps are as follows: adding the waste sponge-derived porous carbon material into deionized water, then adding phosphoric acid, stirring and mixing, and then ultrasonically dispersing, then washing with deionized water and filtering, repeating three times, placing the filter cake in a vacuum drying oven at 80° C. for 12 h, cooling and then taking it out and grinding it, then sending it into a tubular furnace and activating it at 500° C. for 2 h under an inert atmosphere to remove the inadequately bound phosphoric acid, thereby obtaining a waste sponge-derived carbon-based solid acid loaded with phosphate groups;

[0009] Alternatively, the porous carbon material prepared in step (1) is loaded with sulfonic acid groups by a hydrothermal impregnation method, the specific steps being as follows: adding the waste sponge-derived porous carbon material to dichloromethane, followed by adding sulfuric acid or chlorosulfonic acid, and inverting the reaction in a reactor at 50-100° C. (most preferably at 80° C.) for 6 h, washing with deionized water and filtering after the reaction is completed, repeating three times until the filtrate is neutral, and then placing the filter cake in a vacuum drying oven at 80° C. for vacuum drying, cooling, taking it out and grinding it to obtain a waste sponge-derived carbon-based solid acid loaded with sulfonic acid groups;

[0010] (3) The acid-loaded waste sponge-derived carbon-based solid acid prepared in step (2) is mixed with a biomass raw material and placed in a fine quartz tube for catalytic pyrolysis reaction, wherein the mass ratio of the biomass raw material to the waste sponge-derived carbon-based solid acid catalyst is 1:0.1-2, and the heating rate is 10-10 4 ℃ / s, the pyrolysis temperature is 350-850℃, preferably 550-800℃, most preferably 750℃, and the pyrolysis holding time is 10-60s.

[0011] The mass ratio of phosphoric acid, sulfuric acid or chlorosulfonic acid to the waste sponge-derived porous carbon material is 0.1 to 2.

[0012] Preferably, the biomass raw material in step (3) is one of cellulose, cassava residue, bagasse, and poplar residue with a mesh size of 50 to 200, respectively named CE / CA / SU / PO-x, where x represents the mesh size.

[0013] The beneficial effects of the present invention are as follows:

[0014] 1) The present invention utilizes the rich nitrogen-containing functional groups and porous structure of waste sponges to obtain waste sponge-derived carbon-based solid acids through carbonization, acid treatment and other processes for use as catalysts for biomass pyrolysis, which can convert biomass into chemicals such as LG / LGO with high added value, providing a new idea for the comprehensive recycling of biomass;

[0015] 2) The catalyst used in the present invention is prepared from sponges in scrapped car seats. The raw materials are widely available and inexpensive. It can also avoid environmental pollution caused by direct combustion or landfill of waste sponges, and has the dual characteristics of being economically feasible and environmentally friendly.

[0016] 3) Both waste sponges and waste agricultural and forestry biomass belong to the category of solid waste. The catalytic pyrolysis method proposed in the present invention realizes the synergistic coupling transformation between the two wastes, with a short transformation time, thus having a higher transformation efficiency, and provides a theoretical reference for practical applications.

[0017] In summary, the present invention explores an efficient conversion method for preparing high-value-added chemicals by catalyzing the pyrolysis of biomass using a carbon-based solid acid catalyst derived from waste sponge, constructs two representative organic solid waste coupled conversion systems, prepares waste sponge with a high content of impurities and rich nitrogen-containing functional groups into porous carbon materials, and further obtains carbon-based solid acids through acid treatment. Under conditions of rapid catalytic pyrolysis, the biomass raw materials are efficiently converted into LG and LGO, providing a harmless and resource-based approach for the comprehensive recycling of waste sponge components in organic dismantling residues of scrapped vehicles and waste agricultural and forestry biomass. Specific implementation method:

[0018] The following is a further description of the present invention, rather than a limitation of the present invention.

[0019] Embodiment 1:

[0020] (1) The waste sponge was sent to a tube furnace, and the temperature was raised to 650°C at a heating rate of 10°C / min under an inert atmosphere for carbonization for 3 hours. After the reaction was completed, it was naturally cooled and then taken out and ground to 200 mesh. Then, excessive deionized water was added for washing, and the filter cake was filtered three times and vacuum dried at 80°C for 12 hours to obtain a porous carbon material. 10mL of deionized water and 1g of phosphoric acid (H3PO4, 85wt.%) were added to 1g of the porous carbon material, and ultrasonic dispersion was performed for 12 hours, followed by washing and filtering with deionized water, and the filter cake was repeated three times. The filter cake was vacuum dried at 80°C for 12 hours, and after grinding, it was sent to a tube furnace and activated at 500°C for 2 hours under an inert atmosphere to remove the inadequately bound phosphoric acid, and a waste sponge-derived carbon-based solid acid loaded with phosphoric acid groups was obtained, which was recorded as 1PC650-3.

[0021] (2) 200-mesh cellulose (CE-200 particles) and the carbon-based solid acid catalyst prepared in step (1) were uniformly mixed in a mass ratio of 1:1 and then fed into a thermal cracker for 10 4 The temperature was raised to 750°C at a rate of 1.3°C / s and maintained for 20 s. The pyrolysis products were qualitatively and quantitatively analyzed by GC-MS, and the yield of levoglucosan (LG) was 3.2%, and the yield of levoglucosone (LGO) was 28.6%, as shown in Table 1.

[0022] Comparative Example 1:

[0023] The same as Example 1, except that no carbon-based solid acid catalyst was added during the pyrolysis process, and the final LG yield was 18.6%, and the LGO yield was 0.2%.

[0024] Comparative Example 2:

[0025] The same as Example 1, except that porous carbon material that has not been treated with acid was added during the pyrolysis process, and the final LG yield was 19.2%, and the LGO yield was 0.3%.

[0026] Comparative Example 3:

[0027] The same as Example 1, except that the raw material of the porous carbon material is waste cotton cloth with a low nitrogen content. The final LG yield is 15.9% and the LGO yield is 9.8%.

[0028] It can be seen from Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 that the waste sponge-derived carbon-based solid acid catalyst can significantly promote the conversion of LG to LGO, thereby increasing the LGO yield. The catalytic activity is attributed to the synergistic effect of the loaded acidic sites and the nitrogen-containing functional groups of the waste sponge itself.

[0029] Embodiment 2:

[0030] (1) The waste sponge was sent into a tube furnace and heated to 650°C at a heating rate of 10°C / min for carbonization for 3 hours under an inert atmosphere. After the reaction was completed, it was naturally cooled and then taken out and ground into 200 mesh. After washing and filtering three times, the filter cake was vacuum dried at 80°C for 12 hours to obtain a porous carbon material. 1g of the waste sponge-derived porous carbon material was added to 5mL of dichloromethane, followed by 1g of sulfuric acid (98%), and the reaction was turned over at 80°C in a reactor for 6 hours. After the reaction was completed, it was washed with deionized water and filtered, and repeated three times until the filtrate was neutral. Then the filter cake was placed in a vacuum drying oven at 80°C for 12 hours, and after cooling, it was taken out and ground to obtain a waste sponge-derived carbon-based solid acid loaded with sulfonic acid groups, which was recorded as 1SC650-3.

[0031] (2) The CE-200 particles and the carbon-based solid acid catalyst prepared in step (1) were uniformly mixed in a mass ratio of 1:1 and then fed into a thermal cracker for 104 The temperature was raised to 750 °C at a rate of 1.3 °C / s and maintained for 20 s. The pyrolysis products were qualitatively and quantitatively analyzed by GC-MS, and the yield of LG and LGO was 5.9% and 18.4%, respectively, as shown in Table 1.

[0032] Embodiment 3:

[0033] (1) The waste sponge is sent into a tube furnace, and the temperature is raised to 650°C at a heating rate of 10°C / min under an inert atmosphere for carbonization for 3 hours. After the reaction is completed, it is taken out and ground into 200 mesh after natural cooling. After washing and filtering three times, the filter cake is vacuum dried at 80°C for 12 hours to obtain a porous carbon material. 1g of the waste sponge-derived porous carbon material is added to 5mL of dichloromethane, followed by 1g of chlorosulfonic acid (98%), and the reaction is turned over at 80°C in a reactor for 6 hours. After the reaction is completed, it is washed with deionized water and filtered. This is repeated three times until the filtrate is neutral. The filter cake is then placed in a vacuum drying oven at 80°C for 12 hours. After cooling, it is taken out and ground to obtain a waste sponge-derived carbon-based solid acid loaded with sulfonic acid groups, which is recorded as 1S Cl C650-3.

[0034] (2) The CE-200 particles and the carbon-based solid acid catalyst prepared in step (1) were uniformly mixed in a mass ratio of 1:1 and then fed into a thermal cracker for 10 4 The temperature was raised to 750 °C at a rate of 1.3 °C / s and maintained for 20 s. The pyrolysis products were qualitatively and quantitatively analyzed by GC-MS, and the yield of LG and LGO was 8.6% and 15.3%, respectively, as shown in Table 1.

[0035] Embodiment 4:

[0036] Refer to Example 1, except that the biomass raw material is cassava residue.

[0037] (1) The waste sponge was sent to a tube furnace, and the temperature was raised to 650°C at a heating rate of 10°C / min under an inert atmosphere for carbonization for 3 hours. After the reaction was completed, it was naturally cooled and then taken out and ground to 200 mesh. After washing and filtering three times, the filter cake was vacuum dried at 80°C for 12 hours to obtain a porous carbon material. 10mL of deionized water and 1g of phosphoric acid (H3PO4, 85wt.%) were added to 1g of the porous carbon material, and ultrasonic dispersion was performed for 12 hours, followed by washing and filtering, which was repeated three times. The filter cake was vacuum dried at 80°C for 12 hours, and after grinding, it was sent to a tube furnace and activated at 500°C for 2 hours under an inert atmosphere to remove the inadequately bound phosphoric acid, and a waste sponge-derived carbon-based solid acid loaded with phosphoric acid groups was obtained, which was recorded as 1PC650-3.

[0038] (2) The CA-200 particles and the carbon-based solid acid catalyst prepared in step (1) were uniformly mixed in a mass ratio of 1:1 and then fed into a thermal cracker for 10 4The temperature was raised to 750 °C at a rate of 1.3 °C / s and maintained for 20 s. The pyrolysis products were qualitatively and quantitatively analyzed by GC-MS, and the yield of LG and LGO was 3.5% and 24.5%, respectively, as shown in Table 1.

[0039] Embodiment 5:

[0040] Refer to Example 1, except that the biomass raw material is bagasse.

[0041] (1) The waste sponge was sent to a tube furnace, and the temperature was raised to 650°C at a heating rate of 10°C / min under an inert atmosphere for carbonization for 3 hours. After the reaction was completed, it was naturally cooled and then taken out and ground to 200 mesh. After washing and filtering three times, the filter cake was vacuum dried at 80°C for 12 hours to obtain a porous carbon material. 10mL of deionized water and 1g of phosphoric acid (H3PO4, 85wt.%) were added to 1g of the porous carbon material, and ultrasonic dispersion was performed for 12 hours, followed by washing and filtering, which was repeated three times. The filter cake was vacuum dried at 80°C for 12 hours, and after grinding, it was sent to a tube furnace and activated at 500°C for 2 hours under an inert atmosphere to remove the inadequately bound phosphoric acid, and a waste sponge-derived carbon-based solid acid loaded with phosphoric acid groups was obtained, which was recorded as 1PC650-3.

[0042] (2) The SU-200 particles and the carbon-based solid acid catalyst prepared in step (1) were uniformly mixed in a mass ratio of 1:1 and then fed into a thermal cracker for 10 4 The temperature was raised to 750 °C at a rate of 1.3 °C / s and maintained for 20 s. The pyrolysis products were qualitatively and quantitatively analyzed by GC-MS, and the yield of LG and LGO was 3.3% and 23.9%, respectively, as shown in Table 1.

[0043] Embodiment 6:

[0044] Refer to Example 1, except that the biomass raw material is poplar powder.

[0045] (1) The waste sponge was sent to a tube furnace, and the temperature was raised to 650°C at a heating rate of 10°C / min under an inert atmosphere for carbonization for 3 hours. After the reaction was completed, it was naturally cooled and then taken out and ground to 200 mesh. After washing and filtering three times, the filter cake was vacuum dried at 80°C for 12 hours to obtain a porous carbon material. 10mL of deionized water and 1g of phosphoric acid (H3PO4, 85wt.%) were added to 1g of the porous carbon material, and ultrasonic dispersion was performed for 12 hours, followed by washing and filtering, which was repeated three times. The filter cake was vacuum dried at 80°C for 12 hours, and after grinding, it was sent to a tube furnace and activated at 500°C for 2 hours under an inert atmosphere to remove the inadequately bound phosphoric acid, and a waste sponge-derived carbon-based solid acid loaded with phosphoric acid groups was obtained, which was recorded as 1PC650-3.

[0046] (2) The PO-200 particles and the carbon-based solid acid catalyst prepared in step (1) were uniformly mixed in a mass ratio of 1:1 and then fed into a thermal cracker for 104 The temperature was raised to 750 °C at a rate of 1.3 °C / s and maintained for 20 s. The pyrolysis products were qualitatively and quantitatively analyzed by GC-MS, and the yield of LG and LGO was 3.7% and 21.2%, respectively, as shown in Table 1.

[0047] Embodiment 7:

[0048] (1) The waste sponge was sent to a tube furnace, and the temperature was raised to 650°C at a heating rate of 10°C / min under an inert atmosphere for carbonization for 1 hour. After the reaction was completed, it was naturally cooled and then taken out and ground to 200 mesh. After washing and filtering three times, the filter cake was vacuum dried at 80°C for 12 hours to obtain a porous carbon material. 10mL of deionized water and 0.1g of phosphoric acid (H3PO4, 85wt.%) were added to 1g of the porous carbon material, and ultrasonic dispersion was performed for 12 hours, followed by washing and filtering, which was repeated three times. The filter cake was vacuum dried at 80°C for 12 hours, and after grinding, it was sent to a tube furnace and activated at 500°C for 2 hours under an inert atmosphere to remove the inadequately bound phosphoric acid, and a waste sponge-derived carbon-based solid acid loaded with phosphoric acid groups was obtained, which was recorded as 0.1PC650-1.

[0049] (2) The CE-50 particles and the carbon-based solid acid catalyst prepared in step (1) were uniformly mixed at a mass ratio of 1:0.1 and then fed into a thermal cracker, and the temperature was raised to 350°C at a heating rate of 10°C / s and maintained for 10 seconds. The pyrolysis products were qualitatively and quantitatively analyzed by GC-MS, and the LG yield was 1.8% and the LGO yield was 0%, as shown in Table 1.

[0050] Embodiment 8:

[0051] (1) The waste sponge was sent to a tube furnace, and the temperature was raised to 450°C at a heating rate of 10°C / min under an inert atmosphere for carbonization for 3 hours. After the reaction was completed, it was taken out and ground to 200 mesh after natural cooling. After washing and filtering three times, the filter cake was vacuum dried at 80°C for 12 hours to obtain a porous carbon material. 10mL of deionized water and 1g of phosphoric acid (H3PO4, 85wt.%) were added to 1g of the porous carbon material, and ultrasonic dispersion was performed for 12 hours, followed by washing and filtering, which was repeated three times. The filter cake was vacuum dried at 80°C for 12 hours, and after grinding, it was sent to a tube furnace and activated at 500°C for 2 hours under an inert atmosphere to remove the inadequately bound phosphoric acid, and a waste sponge-derived carbon-based solid acid loaded with phosphoric acid groups was obtained, which was recorded as 1PC450-3.

[0052] (2) The CE-200 particles and the carbon-based solid acid catalyst prepared in step (1) were uniformly mixed at a mass ratio of 1:0.5 and then fed into a thermal cracker, and the temperature was raised to 550°C at a heating rate of 100°C / s and maintained for 20s. The pyrolysis products were qualitatively and quantitatively analyzed by GC-MS, and the LG yield was 2.9% and the LGO yield was 13.2%, as shown in Table 1.

[0053] Embodiment 9:

[0054] (1) The waste sponge was sent to a tube furnace, and the temperature was raised to 750°C at a heating rate of 10°C / min under an inert atmosphere for carbonization for 3 hours. After the reaction was completed, it was naturally cooled and then taken out and ground to 200 mesh. After washing and filtering three times, the filter cake was vacuum dried at 80°C for 12 hours to obtain a porous carbon material. 10mL of deionized water and 1g of phosphoric acid (H3PO4, 85wt.%) were added to 1g of the porous carbon material, and ultrasonic dispersion was performed for 12 hours, followed by washing and filtering, which was repeated three times. The filter cake was vacuum dried at 80°C for 12 hours, and after grinding, it was sent to a tube furnace and activated at 500°C for 2 hours under an inert atmosphere to remove the inadequately bound phosphoric acid, and a waste sponge-derived carbon-based solid acid loaded with phosphoric acid groups was obtained, which was recorded as 1PC750-3.

[0055] (2) The CE-200 particles and the carbon-based solid acid catalyst prepared in step (1) were uniformly mixed in a mass ratio of 1:1 and then fed into a thermal cracker for 10 4 The temperature was raised to 750 °C at a rate of 1.3 °C / s and maintained for 20 s. The pyrolysis products were qualitatively and quantitatively analyzed by GC-MS, and the yield of LG and LGO was 3.0% and 25.9%, respectively, as shown in Table 1.

[0056] Embodiment 10:

[0057] (1) The waste sponge was sent to a tube furnace, and the temperature was raised to 850°C at a heating rate of 10°C / min under an inert atmosphere for carbonization for 6 hours. After the reaction was completed, it was taken out and ground to 200 mesh after natural cooling. After washing and filtering three times, the filter cake was vacuum dried at 80°C for 12 hours to obtain a porous carbon material. 10mL of deionized water and 2g of phosphoric acid (H3PO4, 85wt.%) were added to 1g of the porous carbon material, and ultrasonic dispersion was performed for 12 hours, followed by washing and filtering, which was repeated three times. The filter cake was vacuum dried at 80°C for 12 hours. After grinding, it was sent to a tube furnace and activated at 500°C for 2 hours under an inert atmosphere to remove the inadequately bound phosphoric acid, and a waste sponge-derived carbon-based solid acid loaded with phosphoric acid groups was obtained, which was recorded as 2PC850-6.

[0058] (2) The CE-200 particles and the carbon-based solid acid catalyst prepared in step (1) were uniformly mixed in a mass ratio of 1:2 and then fed into a thermal cracker for 10 4 The temperature was raised to 850 °C at a rate of 1.3 °C / s and maintained for 60 s. The pyrolysis products were qualitatively and quantitatively analyzed by GC-MS, and the yield of LG was 0% and the yield of LGO was 17.7%, as shown in Table 1.

[0059] Table 1

[0060]

[0061] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for converting waste sponge-derived carbon-based solid acid-catalyzed pyrolysis of biomass into levoglucosan and levoglucosone, characterized in that: The method comprises the following steps: (1) The waste sponge from scrapped car seats was washed, dried, and crushed, and then sent into a tube furnace. The temperature was raised to 450-850 °C at a heating rate of 10 °C / min under an inert atmosphere and kept at this temperature for 1-6 h for carbonization. After carbonization, the waste sponge was taken out and ground, and then excess deionized water was added, stirred thoroughly, and filtered. This step was repeated three times. The filter cake was collected and vacuum dried at 80 °C for 12 h, then taken out and ground again to obtain the waste sponge-derived porous carbon material; (2) The porous carbon material prepared in step (1) is loaded with phosphate groups by an ultrasonic impregnation method. The specific steps are as follows: the waste sponge-derived porous carbon material is added to deionized water, followed by phosphoric acid, stirred and mixed, and then ultrasonically dispersed, followed by washing with deionized water and filtering, and the process is repeated three times. The filter cake is placed in a vacuum drying oven at 80 °C for 12 h, cooled, taken out, and ground, and then placed in a tubular furnace and activated at 500 °C for 2 h under an inert atmosphere to remove the inadequately bound phosphoric acid, thereby obtaining a waste sponge-derived carbon-based solid acid loaded with phosphate groups; Alternatively, the porous carbon material prepared in step (1) is loaded with sulfonic acid groups by a hydrothermal impregnation method, the specific steps being as follows: adding the waste sponge-derived porous carbon material to dichloromethane, then adding sulfuric acid or chlorosulfonic acid, and inverting the reaction in a reactor at 50-100 °C for 6 h. After the reaction is completed, the reaction is washed with deionized water and filtered, and the reaction is repeated three times until the filtrate is neutral. The filter cake is then placed in a vacuum drying oven at 80 °C for 12 h, and after cooling, taken out and ground to obtain a waste sponge-derived carbon-based solid acid loaded with sulfonic acid groups; (3) The acid-loaded waste sponge-derived carbon-based solid acid prepared in step (2) is mixed with the biomass raw material as a catalyst and placed in a fine quartz tube for catalytic pyrolysis reaction. The mass ratio of the biomass raw material to the waste sponge-derived carbon-based solid acid catalyst is 1:0.1-2, and the heating rate is 10-10 4 °C / s, the pyrolysis temperature is 350~850 °C, and the pyrolysis holding time is 10~60 s.

2. The method according to claim 1, characterized in that: The mass ratio of phosphoric acid, sulfuric acid or chlorosulfonic acid to the waste sponge-derived porous carbon material is 0.1-2.

3. The method according to claim 1, wherein the biomass raw material in step (3) is one of cellulose with a mesh size of 50 to 200, cassava residue, bagasse, and poplar residue.

4. The method according to claim 1, characterized in that When the porous carbon material prepared in step (1) is loaded with sulfonic acid groups by the hydrothermal impregnation method, the reactor temperature is 80 °C.

5. The method according to claim 1, characterized in that: The carbonization temperature of step (1) is 550-650°C.

6. The method according to claim 1, characterized in that The pyrolysis temperature in step (3) is 550-800°C.

7. The method according to claim 1, characterized in that The pyrolysis temperature in step (3) is 750 °C.

Citation Information

Patent Citations

  • Method for preparing levoglucosenone

    CN102250158A

  • Biomass carbon-based solid acid catalyst and preparation method and application thereof

    CN108940313A